Bio-safety technology in production of bovine herpesvirus type 5 (BoHV-5) using an alternative serum-free medium - Cardoso, Tereza C. [UNESP]; Ferrari, Heitor F.; Luvizotto, Maria Cecília R. [UNESP]; Arns, Clarice W. (Science Publications, 2007)
The detection and growth of bovine herpes virus type 5 (BoHV-5) was evaluated in three different media without foetal bovine serum or animal protein by infecting three different cell lines. The OPTI-PRO, VP-SFM and RPMI 1640 media were supplemented by L-glutamine, antibiotics added by 5μg of insulin-like growth factor (IGF-I) and used to adapt CER, MDBK and CRIB cells in a statistic continuous culture system. The results obtained by CRIB and MDBK cells adaptation showed steady growth after 10th passages in OPTI-PRO medium, 20th passages in VP-SFM medium and 30th passages in RPMI 1640 medium, respectively. The OPTI-PRO and RPMI 1640 media were not able to support CER growth, even supplemented by IGF-1 and present apoptotic cells at 72h post-infection. The CER cells seeded after adaptation by 10 th passages in VP-SFM medium added by 5μg/20ml of IGF-1 growth factor revealed the best virus titres compared to MDBK and CRIB cell lines. It was concluded that CER, MDBK and CRIB cells infected by BoHV-5 serotype could be used for laboratory diagnosis propagated on much safer culture system of high biotechnology advances. © 2007 Science Publications.
Keywords: BoHV-5; Bovine herpesvirus; CER cells; CRIB cells; MDBK cells; Serum-free media; Antibiotics; Biotechnology; Cell growth; Diagnosis; Proteins; Bovine herpesvirus type 5 (BoHV-5); Viruses; Animalia; Bovinae; Bovine herpesvirus 5; Herpesviridae